“What Was That All About?” Using Critical Personal Narrative For Inquiry And Critical Reflective Practice - Valerie-Lee Chapman (Adult Education Research Conference, 2004)
I position Critical Personal Narrative (CPN) within the larger field of interpretive narrative inquiry, offer a framework for its use as a research tool, and conclude by suggesting ways CPN can be utilized by adult educators wanting to be critically reflective in their practice. I illustrate this with two stories of discourses at work.